2015
DOI: 10.1007/s11606-015-3290-x
|View full text |Cite
|
Sign up to set email alerts
|

U.S. General Population Estimate for “Excellent” to “Poor” Self-Rated Health Item

Abstract: BACKGROUND:The most commonly used self-reported health question asks people to rate their general health from excellent to poor. This is one of the Patient-Reported Outcomes Measurement Information System (PROMIS) global health items. Four other items are used for scoring on the PROMIS global physical health scale. Because the single item is used on the majority of large national health surveys in the U.S., it is useful to construct scores that can be compared to U.S. general population norms. OBJECTIVE: To es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 22 publications
2
132
0
Order By: Relevance
“…Health status included self-rated health (excellent, very good, good, fair, or poor; Hays, Spritzer, Thompson, & Cella, 2015), depressive symptoms, and number of chronic health problems (out of 10 conditions). The 20-item Center of Epidemiologic Studies-Depression Scale (CES-D) assessed symptoms of depressed mood, feelings of guilt and worthlessness, feelings of helplessness and hopelessness, psychomotor retardation, loss of appetite, and sleep disturbance.…”
Section: Methodsmentioning
confidence: 99%
“…Health status included self-rated health (excellent, very good, good, fair, or poor; Hays, Spritzer, Thompson, & Cella, 2015), depressive symptoms, and number of chronic health problems (out of 10 conditions). The 20-item Center of Epidemiologic Studies-Depression Scale (CES-D) assessed symptoms of depressed mood, feelings of guilt and worthlessness, feelings of helplessness and hopelessness, psychomotor retardation, loss of appetite, and sleep disturbance.…”
Section: Methodsmentioning
confidence: 99%
“…PROMIS has 10 global health questions or items [17] including the widely used excellent to poor general health rating question [18]. The remaining 9 global health items assess physical health (two items), pain, fatigue, general mental health, emotional distress, overall quality of life, and social function (two items).…”
Section: Methodsmentioning
confidence: 99%
“…2 At the same time, patient-reported outcome measures (PROMs) have also clearly shown that improving clinical endpoints (e.g., biomarkers of illness or disease activity) does not always translate into subjective improvement for patients. 1,3 In fact, there are many examples of treatments that significantly alter surrogate biological markers, but have no effect on outcomes of interest to patients: mortality and quality of life.…”
mentioning
confidence: 99%